Risk factors for early childhood dental caries and effects of breastfeeding - Eva Carvajal Roca; Macarena Chofré Llorente; Luis Robledo Díaz; Gisela Senent Vicente (Editorial Ciencias Médicas, 2020)
Introduction: Several factors are described in the literature as determinant in the genesis of early childhood dental caries. However, the role of breastfeeding as a protective factor continues to be a controversial subject. Objective: Determine the risk factors involved in the genesis of early childhood dental caries and the effects of breastfeeding. Methods: A case-control study was conducted of a total 80 patients aged 3-8 years, 35 with dental caries and 45 healthy controls, from the province of Valencia, Spain, selected by nonprobability sampling. The variables analyzed had to do with breastfeeding, sociodemographic characteristics, and eating and hygiene habits. Analysis of quantitative variables was based on arithmetic mean and standard deviation as measures of centrality. Qualitative variables were described in terms of their absolute and relative frequencies. Factors associated to dental caries development were examined with chi-square and odds ratio testing. Results: No statistically significant relationship was found between the variables analyzed and breastfeeding. A relationship could be established between the emergence of dental caries and the educational level of the mother (OR= 4.17) and the father (OR= 4.87), daily sugar intake (OR= 4), smoking mother (OR= 4.23) and gestational age (a greater incidence in preterm deliveries). Conclusions: Breastfeeding is a protective factor against childhood dental caries, though the study could not establish that relationship. The most important factors related to the emergence of dental caries in the study sample were gestational age, educational level of parents, smoking mother and daily sugar intake.